Fungi and Plant Diseases - V.K. Gupta; Y.S.Paul; Satish k. Sharma (Ludhiana Kalyani)
"Fungi and plant diseases" dealing on different aspects of fungi and diseases caused by them
plant diseases caused fungi sramenopila protoctista
Keywords: plant diseases caused fungi sramenopila protoctista